Improving strength and impact resistance of 3D printed components with helicoidal printing direction. (November 2022) - Liu, J.L.; Lim, E.W.L.; Sun, Z.P.; Wang, J.; Tay, T.E.; Tan, V.B.C.
Highlights: 3D printers are configured to print parts with bioinspired helicoidal microstructure. Printing plates with helicoidal structure increase their impact resistance by 128%. Helicoidal plates were even sometimes stronger than compression molded plates. The voids in helicoidal plates divert crack propagation during impact. The improvement in performance comes at no additional cost or fabrication time. Abstract: Inspired by the fibre layup in the exoskeleton of mantis-shrimp, we show that the out-of-plane strength and impact toughness of 3D printed plates can be significantly improved by simply controlling the tool path (printing direction) of each layer to replicate a helicoidal layup. Without any increase in weight or fabrication time, or effects on the final shape, 3D printed helicoidal plates are shown to outperform conventional printed plates by up to 360% and 128% in terms of out-of-plane strength and impact energy dissipation. Moreover, the 3D printed plates with helicoidal layup can sustain 20% higher out-of-plane load than compression moulded plates and possess comparable impact resistance. The damage mechanisms of 3D printed plates are different under static loading and dynamic impact. Helicoidal layup excels in both conditions; the well-distributed voids in helicoidal layups are effective at preventing large crack formations during static loading; while spiralling cracks in the helicoidal layup prevent catastrophic crack propagation during impact. Fibre reinforced laminates have been reported to possess superior mechanical properties when arranged in a helicoidal fashion. This study is performed using plain unreinforced PLA, showing the benefits of such bioinspired substructure are not exclusive to composites.